An Analysis of Students' Strategies in Developing English Vocabulary - Rahayu Sri Wahyuni; Ratmanida Ratmanida (Journal of English Language Teaching, 2020)
This study aimed to highlight the students’ strategies in developing English vocabulary applied by fourth-year English education students of Padang State University and to expose students’ reasons by using vocabulary learning strategies based on Gu and Johnson theory (1996). The instrumentations of this research were questionnaire and interviews. This research used a qualitative descriptive method. The result of this research showed that students used Metacognitive strategies (95,58%), Beliefs strategies (92,34%), and Cognitive strategies (81,78%) to develop their English vocabulary. In more specific, it showed that students were dominated to use five vocabulary learning strategies: 1) Bottom up (98%), 2) Top down (96%), 3) Self-initiation (96%), 4) Selective Attention (95%), and 5) Guessing (95%). It also revealed that there were three points of students’ reasons in using vocabulary learning strategies: 1) Students wanted to know the meaning of the words in detail. 2) Students wanted to remember the new words longer. 3) Students claimed that the strategy they chose was more efficient, comfortable, suitable and understandable strategy.